A Retrospective Postmortem Study of Hyoid Bone Fractures in Mechanical Asphyxial Death - Shivaramu MG; Vijay Kumar AG (Indian Journal of Forensic Medicine & Toxicology, 2021)
In the present study, 11 cases were belongs to 21 to 30 year age group followed by 9 cases belongs to 31-40 year age group. Among patients studied, 54% were males and 46 % were females, in 80% of the cases manner of death was hanging and in 4% of cases was strangulation and 6% of cases was throttling, out of 20 cases of hanging hyoid bone fracture (Anteroposterior compression fracture) was seen in 2 cases and out of 2 cases of strangulation hyoid bone fracture was not found and out of 3 cases of throttling, hyoid bone fracture (Inward compression fracture) was found in all cases.